Supervisory skills of extension managers in Sekhukhune district of Limpopo Province in South Africa - Duvel, G.H. (Gustav Heinrich) (University of Pretoria, 2013)
Dissertation (MInstAgrar (Agricultural Extention))--University of Pretoria, 2008.